Inclusive Islamic Education in Indonesia: Challenges, Theological Foundations, and Institutional Reform - Nur Afif (AL-ISHLAH: Jurnal Pendidikan, 2025)
Inclusive education remains a global challenge, particularly within faith-based institutions where religious values can both enable and inhibit inclusive practices. In Islamic education, principles such as rahmatan lil-‘alamin (mercy for all creation) and ‘adl (justice) offer a theological foundation for inclusivity. However, practical implementation often lags behind these ideals. This study investigates the challenges and opportunities of inclusive education in an Islamic schooling context through a case study at MA Jam’iyyah Islamiyyah in South Tangerang. A qualitative descriptive design was employed, involving classroom observations, document analysis, and semi-structured interviews with school leaders, teachers, and students with disabilities. Thematic analysis was used to identify patterns and barriers. Findings reveal persistent structural and pedagogical challenges, including limited institutional awareness of inclusion, inadequate teacher training, inaccessible facilities, and social segregation of students with disabilities. Although stakeholders express ethical commitment to Islamic values of compassion and justice, these values are often not operationalized in classroom practices or institutional policies. The study highlights the gap between theological ideals and educational realities in Islamic schools. It proposes a multi-level reform framework integrating Islamic ethical principles with inclusive pedagogical strategies, policy alignment, and teacher development. This framework positions inclusive education as both a spiritual obligation and a professional standard within Islamic schooling. By offering a contextual Islamic model for inclusive education, the study contributes to the broader discourse on equity and faith-based schooling. Further research is needed to expand the model across diverse Islamic educational settings.